IDENTIFIKASI PERMASALAHAN PENGELOLAAN MUTU TEH DO UNIT USAHA PERKEBUNAN MALABAR PT. NUSANTARA VIII JAWA BARAT - MAULANA, MOHAMAD (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 3 November 2005, 2012)
Quality has become an important factor for producers facing to global competition environment. This global condition pushed The Malabar Estate as a part of the biggest tea producers in Indonesia, Perkebunan Nusantara VIII Co., to manage the quality of tea in order to satisfy consumers need. When Malabar Estate is managing quality of product, there are some problems facing them. The problems could be come from inside or outside company environment. The objective of this paper is to find out problems that could be happened in managing quality of product, put them into a hierarchy and analyze the problems with Analytical Hierarchy Process Method resulting a priority of problems and causes of the problems as an input for Perkebunan Nusantara VIII Co., especially for Malabar Estate to fix the problems. Teh result of analyze using Analytical Hierarchy Process (AHP) show that the main problems of managing product quality in Malabar Estate are decreasing quality of product, increasing cost of production and decreasing quantity of production. Generally, the problems causes by managing production process, qualification of employment, environment factor, infrastructure and increasing cost of fuel and utilities. The problems causes, in general, intend to controllable causes of problems. That means, the company should take some actions to manage and fix the problems immediately.
Keywords: Global Competition, Quality, Quantity, Cost, Consumer Satisfaction.